Colors from Ceylon: a design exhibit of sustainable textiles dyed with coconut husk waste. - Ratnayaka, Nadeeshani (Kansas State University, 2022)
Inheriting tradition is an aspect of slow design that explores ways to sustain lost art and tradition. Even though natural dyeing was heavily practiced in Sri Lanka, most of the country’s textile and craft industry has diverted to using synthetic dyes that are bad for the environment. Many domestically used coconut husks in Sri Lanka are thrown away as waste which can be used as a source of natural dyes for textiles. The purpose of this study was to explore the dyeing potential and surface design possibilities of coconut (Cocos nucifera) husk fiber, a traditional dye source of Sri Lanka. A practice-based design approach was utilized for the project with weekly analysis and reflection on the collected data to move the design process forward. The research was conducted in four stages: dye experimentation, print design exploration, textile art, and exposition. Coconut husks were boiled in water to extract the dyes. Four pre-treatment methods such as aluminum acetate, gallnut, pomegranate, and henna were used for cellulose and potassium aluminum sulfate was used for silk fabrics to enhance the bond between fiber and dye. To increase the color range, iron and citric acid were used as post-treatments. The leftover dye bath was recycled to separate the pigment from the water to create a thickened dye paste that could be used to create surface prints. All the fabrics dyed in pink beige color with slight hue variations except for the fabrics that were pretreated with henna which turned out to have a yellow cast or nude color. During post-treatment iron-treated swatches had a greyish tone and citric acid treatment turned the swatches to a pale orange shade. The thickened dye paste consistency worked best with screen-printing leaving clear lines around the edges of the prints. Based on the findings, a collection of artifacts was developed in the form of textile art. The process and outcomes of the study were displayed in a gallery exhibit to create awareness of the craft of natural dyeing and promote using coconut husk waste as a sustainable dye option. All the selected fabrics performed well in the evenness of dye uptake and saturation between all the pre and post-treatment methods and surface printing quality. There was no color loss after hand washing indicating appropriate dye concentration and good dye to fiber bond. Therefore, coconut husk waste can be considered a good source of natural dye. The exposition served its purpose in promoting public recognition and developing public knowledge in the use of coconut husks to produce natural dyes.
Keywords: Natural dye; Textile design; Coconut husk dye; Sustainable fashion; Screen-printing